THE DIFFERENCES OF LEARNING READINESS AND AUDIO VISUAL MEDIA INFLUENCES ON ECONOMIC LEARNING OUTCOMES OF THE STUDENT IN X GRADE OF SMA NEGERI 3 SURAKARTA AND SMA AL ISLAM 1 SURAKARTA IN THE ACADEMIC YEAR 2016/2017 - Villa Santika; Baedhowi Baedhowi; Muhammad Sabandi (Department of Economics Education, Universitas Sebelas Maret, 2017)
The research aims to know: (1) partial influence of learning readiness and audio visual media on the learning outcomes of the students in X grade of SMA Negeri 3 Surakarta and SMA Al Islam 1 Surakarta, (2) simultan influence of learning readiness and audio visual media on the learning outcomes of the students in X grade of SMA Negeri 3 Surakarta and SMA Al Islam 1 Surakarta (3) the difference of influence of learning readiness and audio visual media on economic learning outcomes of the student in X grade of SMA Negeri 3 Surakarta and SMA Al Islam 1 Surakarta. The population is all students of X grade who get economic subjects in SMA Negeri 3 Surakarta. The total of the students are 351 students with 78 students as a sample and SMA Al Islam 1 Surakarta with 177 students choose 64 students as a sample. The instrument to collect data on this research is a questionnaire and data analysis device is SmartPLS Version 2.0 M3.Based on the effective contribution partial influence of learning readiness to learning outcomes in SMA Negeri 3 Surakarta with value 33,70% is higher than SMA Al Islam 1 Surakarta with value 22,47%. Meanwhile the influence of audio visual media on learning outcomes in SMA Al Islam 1 Surakarta with value 9,63% is higher than SMA Negeri 3 Surakarta with value 8,99%. The simultaneous effect of learning readiness and audio visual media on the learning outcomes of the student in SMA Negeri 3 Surakarta was 42,7% compared to SMA Al Islam 1 Surakarta with value 32,1%. Therefore, there are the differences of influence in both partially and simultaneously the influence of the learning readiness and audio visual media on economic learning outcomes of the students in X grade of SMA Negeri 3 Surakarta and SMA Al Islam 1 Surakarta.